Low-level laser therapy effects on pain perception related to the use of orthodontic elastomeric separators - Furquim,Rachel D'Aurea (2015)
INTRODUCTION: Some patients refer to pre-banding orthodontic separation as a painful orthodontic procedure. Low-level laser therapy (LLLT) has been reported to have local analgesic effect. OBJECTIVE: The aim of this single-blind study was to investigate the perception of pain caused by orthodontic elastomeric separators with and without a single LLLT application (6J). METHODS: The sample comprised 79 individuals aged between 13 and 34 years old at orthodontic treatment onset. Elastomeric separators were placed in first maxillary molars at mesial and distal surfaces and kept in place for three days. The volunteers scored pain intensity on a visual analogue scale (VAS) after 6 and 12 hours, and after the first, second and third days. One third of patients received laser applications, whereas another third received placebo applications and the remaining ones were controls. Applications were performed in a split-mouth design. Thus, three groups (laser, placebo and control) were assessed. RESULTS: No differences were found among groups considering pain perception in all periods observed. CONCLUSION: The use of a single-dose of LLLT did not cause significant reduction in orthodontic pain perception. Overall pain perception due to orthodontic separator placement varied widely and was usually mild.